Development in Digital Capitalism: Challenges and Prospects of Nepal - Pokharel, Suman (KMC Research Journal, 2023)
This study delves into the challenges and possibilities surrounding the establishment of digital capitalism in Nepal. Utilizing a secondary data analysis methodology, it examines the current state of digital capitalism in the country and identifies the key obstacles and opportunities. The theoretical framework employed incorporates concepts like transnational informational capitalism, digital governance, and actor-network theory to comprehend the dynamic relationship between labor, technology, and capitalism in the digital era. The findings indicate that while Nepal has witnessed growth in internet penetration and mobile phone usage, there are still significant disparities in digital access and infrastructure between urban and rural areas. The challenges faced include inadequate digital infrastructure, limited consumer trust and awareness, and the need for more robust regulatory frameworks. Nevertheless, Nepal also holds promising prospects for digital capitalism. The increasing availability of smart-phones a techno-literate youth population, and government initiatives aimed at promoting digital literacy and entrepreneurship contribute to the country's potential in this area. The study underscores the significance of digital capitalism for Nepal's economic development and provides recommendations to policymakers, entrepreneurs, and researchers on how to foster an environment that facilitates the growth of digital capitalism. By addressing the challenges of digital infrastructure, building consumer trust, and strengthening regulatory frameworks, Nepal can harness the benefits of digital capitalism, leveraging it as a catalyst for economic progress in the country.